1980
DOI: 10.1002/j.1551-8833.1980.tb04573.x
|View full text |Cite
|
Sign up to set email alerts
|

Well Water Quality Deterioration in Central Pierce County, Washington

Abstract: Currently 20 percent of US water consumption is supplied by groundwater, and its contamination is causing considerable alarm. In densely populated Central Pierce County (Wash.), groundwater contamination was found to originate from septic tank drainfields. The highest nitrate and coliform concentrations in groundwater occur when infiltrating rainfall dissolves and leaches these contaminants downward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Rainfall mobilizes previously retained bac teria and viruses and greatly promotes their transport in groundwater. Sev eral studies have shown that the greatest degree of drinking water well contamination occurs after periods of heavy rainfall [23][24][25].…”
Section: Fate Of Pathogens In the Subsurfacementioning
confidence: 99%
See 1 more Smart Citation
“…Rainfall mobilizes previously retained bac teria and viruses and greatly promotes their transport in groundwater. Sev eral studies have shown that the greatest degree of drinking water well contamination occurs after periods of heavy rainfall [23][24][25].…”
Section: Fate Of Pathogens In the Subsurfacementioning
confidence: 99%
“…While presence of fecal bacteria was much less common in deeper wells, some wells as deep as 250 ft (80 m) were positive. Increased levels of bacterial contamination of drinking well water after periods of rain have been noted in several studies [23][24][25]45]. In one study, it was noted that while an increase in coliform bacteria appears almost immediately after periods of heavy rainfall in shallow wells, in deeper wells the increase did not occur until 2 weeks later [46].…”
Section: Saltsmentioning
confidence: 99%